Kolonial lejlighedsdigtning mellem Grønland og København 1729-30 - Andersen, Emil (Historisk Tidsskrift, 2025)
This article examines six hitherto unpublished pieces of occasional poetry written in Danish by Missionary Hans Egede and Secretary Henrik Brunsvig for the royal birthday celebrations in Greenland’s Danish-Norwegian colonial settlements. Penned in 1729 and 1730, the poems (along with two published elsewhere and several others, mentioned in primary sources but now lost) yield insights into two conflicting patron-client networks connecting the Greenland colony to the government in Copenhagen, headed by Governor Claus Enevold Paars and Commandant Jørgen Brodersen Landorph, respectively. The poems’ themes and messages highlight the ideological foundations of Greenland ‘crown colony’ governance (in function between 1728 and 1731), based on historical understandings of Greenland as a dependency of Denmark-Norway. Finally, the transmission of the poems sheds light on the practices, dynamics and interactive strategies of colonial agents and imperial powerholders in the early phase of Denmark’s colonisation of Greenland.